Dialog chrześcijaństwa z islamem - Wąs, Adam (Studia Nauk Teologicznych PAN, 2020)
Since the beginning of islam in the 7th century christians and Muslims have been a permanent challenge for themselves. the confrontation and the closeness which accompany them through the entire history are rooted in the universal and monotheistic character of both religions. From the christian point of view it would be diffcult to talk about interreligious dialogue or at least its modern developments, without the Second Vatican council (1962–1965) and the declaration nostra aetate. the council recognized in it the spiritual, moral and cultural values present in different religions, emphasizing spiritual and moral values between Muslim and christians. For the frst time in the history of the catholic church, the council’s fathers offcially called for the co-operation with Muslims. this is the starting point of the real dialogue between christians and Muslims. This article attempts to describe and analyse – in three parts – some aspects of the dialogical initiatives of christian-Muslim relations. A greater part of it refers to the roman catholic church, but some examples of interpretation and dialogical initiatives of the Orthodox and protestant churches are included as well. Islam as a point of reference is taken as a whole. After a short introduction containing a general defnition of dialogue and its interreligious form the frst part deals with historical facts which shaped the dialogical attitudes. the selected historical facts build a background for some theological ideas on islam in orthodox, catholic and protestant traditions. The second part focuses on the practical aspects of dialogue – its forms and representative institutions, i.e. the pontifcal council for interreligious Dialogue, World council of churches and Orthodox center of the ecumenical patriarch in chambésy which are engaged in the dialogue on behalf of the main christian churches. the third part offers some ideas concerning aarguments for dialogue, its effciency and quality which might be important for the future of dialogue. the modern history of christian-Muslim relations shows that the dialogue between adherents of these two largest religions is possible despite that it is not an easy undertaking. the author underlines that there is no alternative to dialogue as there is no better way to defeat prejudices and heal the wounds of the past.